Annoyance evaluation of noise emitted by urban substation - Li Jun (SAGE Publishing, 2021)
In China, noise pollution from substations in urban areas is becoming more and more serious. An annoyance evaluation of the noise emitted by urban substations is presented. First, the subjective evaluation is conducted on the noise samples from urban substations via the semantic differential method. Subsequently, according to the typical characteristics of urban substation noise, 14 acoustical metrics are used to describe the noise samples for objective evaluation. Then the correlation analysis and regression analysis between the objective and subjective evaluation results are carried out. Finally, a regression model for urban substation noise evaluation is established. Practical application shows that the regression model can correctly predict the subjective annoyance of urban substation noise.